Sociology of Health and Illness: A comparison field Study between Rural and Urban: Wasit Province - Rzew, Sabreen Mohammed; mahdi, Majida shaker (Al-Adab Journal, 2021)
The most important of the study: It was found that respondents and of the total sample units answered yes, which is the highest percentage, which is considered the family is the social environment that works to instill health education among its members in the countryside. In urban areas, respondents were interviewed and of the total sample units were yes. The family is considered the social environment that instills health education among its members, as evidenced by the fact that both rural and urban areas considered the family to be the social environment in which Is working to instill health education among its members, but the rural population recorded the highest proportion of urban. were interviewed and of the total sample units were found to be different behavior of the family in dealing with its members when the disease in the countryside. In urban areas, respondents responded with of the total sample units. Yes, they also find a difference in the behavior of the family in dealing with its members at the time of illness. As a result, the rural and urban areas registered the highest percentage of yes. However, rural areas are higher than urban areas. respondents of the total sample units do not agree with the occurrence of diseases in the family due to the death of a relative in the countryside, followed by the urban side with respondents and of the total The sample units do not agree with the diseases that occur in the family due to the death of a relative. As a result, the highest percentage of respondents in rural areas is higher than urban, ie they do not agree with the occurrence of diseases in the family due to the death of a relative. and of the total sample units do not agree that the individual exposure to social isolation leads to illness in the countryside, followed by the urban side with respondents and of the total sample units Do not agree with the individual exposure to social isolation lead to the disease, and we conclude that the countryside recorded the highest proportion of urban exposure to isolation as a result of the disease. of the total sample units. All of the family members took care of the patient in the countryside, followed by the urban side, with respondents and of the total sample units taking the whole family attention We all conclude that the rural and urban scored the highest percentage of the answer, yes, that the family members all of them take care of the patient now that the rural compared to the urban were the highest in the answer. and of the total sample units do not consider the incidence of the disease to lead to the instability of family life socially in the countryside, followed by the urban side with respondents and of Total sample units do not consider the disease to lead to the instability of family life socially. It results from the fact that urban recorded the highest percentage of rheumatoid.